Single-cell transcriptomics reveals systemic immune dysregulation in non-segmental vitiligo - Xiao, Jialing; Guo, Xiaojuan; Gong, Lingxue; Li, Qinhui; Dong, Kai; Guo, Xiaoxin; Li, Huan; Wang, Ting; Wang, Liang; Wu, Weijia; Gan, Chengzi; Li, Mingze; et al. (Frontiers in Immunology, 2025)
BackgroundNon-segmental vitiligo (NSV) is an autoimmune disorder characterized by irregular depigmented skin patches due to melanocyte loss, which causes considerable psychosocial burden. Although localized mechanisms underlying vitiligo pathogenesis have been studied extensively, investigations into peripheral blood mononuclear cells (PBMCs), key mediators of autoimmune diseases, remain limited.MethodsTo address this gap, we performed single-cell RNA sequencing (scRNA-seq) on peripheral blood samples from 3 untreated patients with generalized, progressive non-segmental vitiligo (GP-NSV) and 3 healthy controls. Findings were validated using flow cytometry in an additional cohort of 7 GP-NSV patients and 30 controls. Computational analyses, including pseudotime trajectory reconstruction and pathway enrichment, were employed to characterize immune cell subsets and their functional states.ResultsVitiligo patients exhibited striking heterogeneity in PBMC subsets. KLRC2+ NK cells were markedly reduced and enriched in tumor necrosis factor (TNF) and apoptotic signaling pathways, a finding further confirmed by flow cytometry. Pseudotime analysis indicated that NK cells underwent negative regulation of DNA metabolic processes alongside activation of granzyme-mediated programmed cell death. In addition, the frequency of FCGR3A+ Cytotoxic CD8+T cell was reduced, with enrichment in T cell activation and differentiation signatures. STAM+ regulatory T cells (Tregs) were increased, whereas EGR1+ B cells were decreased, both subsets showing enrichment in pathways linked to osteoclast differentiation and calcium ion metabolism, suggesting a potential role of calcium homeostasis dysregulation in disease pathogenesis.ConclusionsThis study provides the single-cell atlas of PBMCs in GP-NSV, uncovering profound transcriptional and compositional alterations across multiple immune cell subsets in active vitiligo. These findings offer novel insights into systemic immune dysregulation in GP-NSV and pave the way for novel targeted therapeutic strategies.